Integration of Religion and Culture in Muslim Minority Communities through Islamic Education - Muhammad Darwis Dasopang; HJ Sammali bin HJ Adam; Ismail Fahmi Arrauf Nasution (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
The clash between Islam and culture often occurs in efforts to disseminate Islamic education to the society especially in areas with Muslim minority communities. This study aims to explore the integration of culture and Islam in Muslim minority areas in the context of implementing Islamic education. The research took place at two Madrasah Aliyah schools and one Madrasah Tsanawiyah located in Tarutung City. This study applied qualitative and phenomenological approach. The data were obtained through observation, interviews, and documentation techniques. Triangulation techniques were used to analyze the data. The informants involved in this study were community leaders, educational leaders and religious leaders. The results of the study show that Islamic religion and culture can be integrated in socializing Islamic education to people in Muslim minority areas in Indonesia. Many aspects of Batak culture are maintained because they are in accordance with Islamic religious teaching. Some aspect of Batak culture that are contrary to Islamic religious teachings are adapted to be compatible with Islamic religious teachings. In this study, the integration of Islamic religion and Batak culture went fairly smoothly and is accepted by the community to deliver in Islamic education in the region.